PERAN ETOS KERJA DAN DISIPLIN KERJA DALAM MEMBANGUN KINERJA KARYAWAN [THE ROLE OF WORK ETHIC AND WORK DISCIPLINE IN BUILDING EMPLOYEE PERFORMANCE] - Utomo, Styo Budi (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to analyze the role of work ethic and work discipline in building employee performance at the Regional Office II of the Meteorology, Climatology, and Geophysics Agency in South Tangerang. The research employed a descriptive quantitative approach involving all 83 employees as respondents using a saturated sampling (census) technique. Primary data were collected through questionnaires and analyzed using SPSS version 25, applying correlation analysis, multiple linear regression, coefficient of determination, as well as t-test and F-test. The results indicate that work ethic makes a significant contribution to employee performance, as reflected by a t-value of 12.747 with a significance level of 0.000, while work discipline also shows a significant contribution with a t-value of 14.768 and a significance level of 0.000. Simultaneously, work ethic and work discipline play a significant role in building employee performance, as evidenced by an F-value of 218.102 exceeding the F-table value of 3.11. The multiple correlation coefficient of 0.865 indicates a strong association, with the regression equation Y = 3.483 + 0.299X₁ + 0.600X₂. Furthermore, the coefficient of determination of 0.729 suggests that 72.9% of the variance in employee performance is explained by work ethic and work discipline, while the remaining 27.1% is influenced by other factors outside the research model.